2001
DOI: 10.1200/jco.2001.19.15.3539
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Stratification Factor Prognostic for Survival in Advanced Cancer: The Good/Bad/Uncertain Index

Abstract: The GBU index may be recommended as a supplementary stratification factor for certain future phase III trials in metastatic lung or colorectal cancer where patient heterogeneity is a particular concern. The GBU represents a relatively modest increase to the cost and patient burden of a clinical trial given the additional control that is achieved over the potentially confounding concomitant to the treatment variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…These results are consistent with findings from other studies. 9,32,34,35 Second, we found that the LASA items correlated strongly with similar scales on other, wellvalidated, multi-item scales that are frequently used in cancer patients, thereby supporting the concurrent validity and construct validity of the LASA. Specifically, the Overall QOL LASA item correlates strongly with the overall score on the FACT-Br, the Overall SDS score, and the Overall POMS score.…”
Section: Discussionmentioning
confidence: 67%
“…These results are consistent with findings from other studies. 9,32,34,35 Second, we found that the LASA items correlated strongly with similar scales on other, wellvalidated, multi-item scales that are frequently used in cancer patients, thereby supporting the concurrent validity and construct validity of the LASA. Specifically, the Overall QOL LASA item correlates strongly with the overall score on the FACT-Br, the Overall SDS score, and the Overall POMS score.…”
Section: Discussionmentioning
confidence: 67%
“…For example, significant differences in the assessment of performance status have been reported between oncologists, nurses and patients, oncologists being the most optimistic in their assessment and patients the least (Ando et al, 2001). As a result there is continuing interest in the development of prognostic scores, which better reflect clinical outcome (Bennett and Ryall, 2000;Sloan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, significant differences in the assessment of performance status have been reported between oncologists, nurses and patients, oncologists being the most optimistic in their assessment and patients the least (Ando et al, 2001). There is therefore a continuing interest in prognostic factors, which better reflect response to treatment and survival (Bennett and Ryall, 2000;Sloan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%